Opinion seeking behaviour of healthcare providers in ambulatory cardiovascular care in Germany: a cross-sectional study - Hennrich, Patrick; Arnold, Christine; Traulsen, Pia; Peters-Klimm, Frank; Wensing, Michel (BMC health services research, 2022)
Healthcare providers’ inclination to seek or lead other providers’ opinions on clinical topics may influence healthcare practices, particularly regarding their alignment across different providers in controversial domains. This study aimed to explore opinion-seeking behaviours of general practitioners and their impacts on clinical opinions in ambulatory cardiovascular care in Germany.
Gesehen am 28.11.2022